Preparation and tribological properties of MoS2/graphite composite coatings modified by La2O3. Issue 8 (12th November 2018) - Qiu, Ming; Zhang, Rui; Li, Yingchun; Du, Hui; Pang, Xiao Xu
Abstract : Purpose: The MoS2 /graphite composite coatings modified by La2 O3 through spraying technique were successfully prepared on the inner rings of spherical plain bearings. As a comparison, unmodified coatings were also prepared. This paper aims to study the La-modified MoS2 /graphite composite coating experimentally and improve the tribological performance of self-lubricating spherical plain bearings. Design/methodology/approach: The performance of La2 O3 toward the friction coefficient, temperature rise and wear rate of the coatings was studied by a self-made tribo-tester under different swing cycles. And the texture, surface morphology and element composition of the coatings were characterized by scanning electron microscope, energy dispersive spectroscopy and X-ray diffractometry. Findings: The additives La2 O3 refined the coatings' microstructure and improved the tribological properties of the coatings. The oxidation of Mo + 4 to Mo + 6 was effectively inhibited. And the amount of abrasive grains, peeling pits and local cracks on the coatings surface decreased and homogeneous lubricating films formed, which were attributed to the existence of La2 O3 . The wear mechanisms of unmodified coatings were severe abrasive wear, adhesive wear and delamination wear. However, it exhibited superior wear resistance of the La-modified coatings to unmodified coatings, presenting slight abrasive wear and adhesive wear. The service life of bearings was prolonged under the protection of the modified coatings. Originality/value: The paper proposed a new modified MoS2 /Graphite composite coating for the self-lubricating spherical plain bearings. The investigation on the friction, wear and temperature increase behaviors and the wear mechanisms of the coatings are beneficial to prolonging the service life of the self-lubricating spherical plain bearings.